Cellulose acetate nanocomposite ultrafiltration membranes tailored with hydrous manganese dioxide nanoparticles for water treatment applications. (21st April 2019) - Vetrivel, Selvaraj; Rana, Dipak; Sri Abirami Saraswathi, Meenakshi Sundaram; Divya, Kumar; Kaleekkal, Noel Jacob; Nagendran, Alagumalai
Abstract : Hydrous manganese dioxide (HMO) nanoparticles incorporated cellulose acetate (CA) composite ultrafiltration (UF) membranes are prepared with the aim of improving the water permeation and BSA contaminant removal. The HMO nanoparticles are synthesized from manganese ion and characterized by FT‐IR, XRD, and FESEM. The effect of variation of HMO on CA membranes is probed using FT‐IR, EDAX, contact angle, SEM, and AFM analysis to demonstrate their chemical functionality, hydrophilicity, and morphology. CA/HMO membranes are showing the enhancement in pure water flux (PWF), water uptake, porosity, hydrophilicity, fouling resistance, BSA rejection, and flux recovery ratio (FRR). CA‐1 membrane displayed higher PWF (143.6 Lm 2 h −1 ), BSA rejection (95.9%), irreversible fouling (93.3%), and FRR (93.3%). Overall results confirmed that the CA/HMO nanocomposite UF membranes overcome the bottlenecks and shows potential for water treatment applications.